An Assessment on the Readiness of the Philippine Domestic Shipping for the Implementation of Sulfur Cap Regulation under MARPOL Annex VI - Mylyn Cardines (Future Science / FSH-PH Publications, 2026)
The study assessed the readiness of the Philippine domestic shipping sector for the implementation of the sulfur cap regulation under MARPOL Annex VI, focusing on Amoroso’s dimensions of readiness: cultural refers to awareness and acceptance, structural that refers to the institutional and resources capacity and operational which refers to implementation capability. It examined the regulatory requirements, national policies, stakeholder awareness, capability-building initiatives, implementation and enforcement mechanisms, international and regional best practices, availability of incentives and funding, perceived challenges and measures to support compliance. Mixed methods approach was employed, using a concurrent triangulation design wherein qualitative and quantitative data were collected simultaneously and integrated during analysis to provide a comprehensive assessment of readiness. The findings revealed that the Philippines has a well-defined regulatory framework and a generally adequate level of stakeholder awareness. However, significant gaps remain in technical understanding, financial support mechanisms, and enforcement capacity. Capability-building initiatives are present but require enhancement, particularly through practical and scenario-based training. Although implementation follows a multi-agency approach, inconsistencies in enforcement and limited monitoring resources affect its effectiveness. Furthermore, the absence of dedicated financial incentives places additional burden on shipping companies, especially small and medium-sized operators. The study concludes that the Philippine domestic shipping sector is partially ready for sulfur cap implementation. Strengthening inter-agency coordination, capability-building programs, monitoring infrastructure, and financial support mechanisms is recommended to promote effective and sustainable compliance.